Relationships Between Teaching Experience and Teaching Ability with TPACK: Perceptions of Mathematics and Science Lecturers at an Islamic University - Muhammad Haviz; Ika Metiza Maris; Elda Herlina (Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to measure Islamic university mathematics and science lecturers (IU-MSLs) perception of technological pedagogical content knowledge (TPACK) in 21st-century learning. This research utilized a quantitative method derived from a descriptive survey collected from 48 lecturers at a single university. Confirmatory factor analysis (CFA) and alpha Cronbach methods were applied to determine the quality of the instruments used in this study. Furthermore, descriptive statistics and ANOVA were used to analyze the data obtained, while correlations were used to test the hypotheses. The results showed no relationship between teaching experience (TE) and teaching ability (TA) with TPACK. In addition, there were no differences in lecturers' perceptions of TPACK based on the material being taught. This study concluded that TPACK is an essential competency for mathematics and science lecturers in an Islamic university.